2004
DOI: 10.1037/0096-3445.133.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Music, Pandas, and Muggers: On the Affective Psychology of Value.

Abstract: This research investigated the relationship between the magnitude or scope of a stimulus and its subjective value by contrasting 2 psychological processes that may be used to construct preferences: valuation by feeling and valuation by calculation. The results show that when people rely on feeling, they are sensitive to the presence or absence of a stimulus (i.e., the difference between 0 and some scope) but are largely insensitive to further variations of scope. In contrast, when people rely on calculation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
237
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(258 citation statements)
references
References 38 publications
(45 reference statements)
19
237
0
2
Order By: Relevance
“…The current research replicates and extends the work of Hsee and Rottenstreich (2004) in two studies. Study 1 replicates scope insensitivity effects on donation behavior by comparing differences in consumers primed to make valuations by feelings with those primed to make valuations by calculation.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The current research replicates and extends the work of Hsee and Rottenstreich (2004) in two studies. Study 1 replicates scope insensitivity effects on donation behavior by comparing differences in consumers primed to make valuations by feelings with those primed to make valuations by calculation.…”
Section: Introductionsupporting
confidence: 71%
“…For instance, Desvousges et al (1993) found no differences between participant donations to help save 2000, 20,000, or 200,000 birds. Hsee and Rottenstreich (2004) demonstrated that scope is neglected when valuations are made based on feelings and emotion, whereas valuations based on calculation lead to greater scope sensitivity. This effect is based on the affective focus of the decision maker (Hsee & Rottenstreich, 2004), where the degree to which an individual attends to affective information impacts whether scope or emotion drives donation behavior.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rottenstreich and Hsee (2001) documented a larger insensitivity to changes in the probability scale for affect-rich outcomes (a $500 coupon that could be redeemed toward expenses associated with holidays in Europe) than for affect-poor outcomes (a $500 coupon that could be used toward tuition payments at the university). A similar effect (i.e., a larger insensitivity to changes in numerical features of risky prospects) emerges when the magnitude of a stimulus (e.g., monetary value) is evaluated by feelings rather than by calculation (Hsee & Rottenstreich, 2004). In the same vein, it has recently been shown that people pay less attention to probability information in affectrich than affect-poor decision problems what results in suboptimal choices (Pachur & Galesic, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Specifically, they show that depending on the question asked, experimental groups either required payment or were willing to pay in order to listen to a professor with little oratory or performance skill read poetry aloud. This idea can also be seen when Hsee and Rottenstreich (2004) asked people how much they would pay for CDs. By priming study participants (through a questionnaire) to generate a valuation through either calculation or feeling, they were able to show significantly different value functions for sets of Madonna CDs of varying sizes.…”
Section: Willingness To Pay As An Uncertain Judgment Is Subject To Anmentioning
confidence: 98%